Permanent soil covers on rainfall erosion - Dedecek, Renato Antonio (Pesquisa Agropecuaria Brasileira, 2014)
To characterize the action of different permanent soil covers on controlling erosion, the following treatments were tested, on a Dark-Red Latosol (Haplustox) clay textured and with 5,5% of slope: a. bare soil in fallow condition; b. soil in fallow condition and suspended artificial cover; c. soil in fallow condition and artificial cover on topsoil. Being a year of low and not well distributed rainfall, causing little development of the annual cropping canopy, the need of permanent soil cover was even more evident. While the canopy of the annual crops reduced soil losses at maximum around 50%, suspended soil cover reduced the losses in 85% compared to the test plot-bare soil. The direct impact of raindrops on soil accounted to 87, 6% of the soil losses on bare soil plot. The effect of soil cover were less effective on the soil losses by splash. Correlating soil losses by splash with those observed on soil erosion plots, the importance of the raindrop impact on erosion were confirmed.